Altering microtubule stability affects microtubule clearance and nuclear extrusion during erythropoiesis. Issue 11 (4th April 2019) - Xie, Songbo; Yan, Bing; Feng, Jie; Wu, Yuhan; He, Na; Sun, Lei; Zhou, Jun; Li, Dengwen; Liu, Min
Abstract: Mammalian erythrocytes are highly specialized cells that have adapted to lose their nuclei and cellular components during maturation to ensure oxygen delivery. Nuclear extrusion, the most critical event during erythropoiesis, represents an extreme case of asymmetric partitioning that requires a dramatic reorganization of the cytoskeleton. However, the precise role of the microtubule cytoskeleton in the enucleation process remains controversial. In this study, we show that microtubule reorganization is critical for microtubule clearance and nuclear extrusion during erythropoiesis. Using a rodent anemia model, we found that microtubules were present in erythroblasts and reticulocytes but were undetectable in erythrocytes. Further analysis demonstrated that microtubules became disordered in reticulocytes and revealed that microtubule stabilization was critical for tubulin degradation. Disruption of microtubule dynamics using the microtubule‐stabilizing agent paclitaxel or the microtubule‐destabilizing agent nocodazole did not affect the efficiency of erythroblast enucleation. However, paclitaxel treatment resulted in the retention of tubulin in mature erythrocytes, and nocodazole treatment led to a defect in pyrenocyte morphology. Taken together, our data reveals a critical role for microtubules in erythrocyte development. Our findings also implicate the disruption of microtubule dynamics in the pathogenesis of anemia‐associated diseases, providing new insight into the pathogenesis of the microtubule‐targeted agent‐associated anemia frequently observed during cancer chemotherapy. Abstract : In this study, we reveal that microtubule reorganization is critical for microtubule clearance and nuclear extrusion during erythropoiesis. Although disruption of microtubule dynamics does not affect the efficiency of erythroblast enucleation, microtubule stabilizers suppress microtubule clearance in mature erythrocytes, whereas microtubule destabilizers lead to atypical partitioning of microtubules, indicative of a defect in nuclear partitioning.